Molecular profiling of metastatic breast cancer and target-based therapeutic matching in an Asian tertiary phase I oncology unit - Walsh, Robert John; Ong, Rebecca; Cheo, Seng Wee; Low, Peter Q.J.; Jayagopal, Aishwarya; Lee, Matilda; Ngoi, Natalie; Ow, Samuel G.; Wong, Andrea L.A.; Lim, Siew Eng; Lim, Yi Wan; Heong, Valerie; et al. (Frontiers in Oncology, 2024)
Introduction Molecular profiling of metastatic breast cancer (MBC) through the widespread use of next generation sequencing (NGS) has highlighted actionable mutations and driven trials of targeted therapy matched to tumour molecular profiles, with improved outcomes reported using such an approach. Here, we review NGS results and treatment outcomes for a cohort of Asian MBC patients in the phase I unit of a tertiary centre. Methods Patients with MBC referred to a phase I unit underwent NGS via Ion Ampliseq Cancer Hotspot v2 (ACH v2, 2014-2017) prior to institutional change to FoundationOne CDx (FM1, 2017-2022). Patients were counselled on findings and enrolled onto matched therapeutic trials where available. Outcomes for all subsequent treatment events were recorded to data cut-off 31/1/2022. Results A total of 215 patients were enrolled with successful NGS in 158 patients. The PI3K/AKT/PTEN pathway was the most altered with one or more of the pathway member genes PIK3/AKT/PTEN affected in 62% (98/158) patients, and 43% tumours harbouring a PIK3CA alteration. Tumour mutational burden (TMB) was reported in 96/109 FM1 sequenced patients, mean TMB 5.04 mt/Mb and 13% (12/96) with TMB 10mt/Mb. Treatment outcomes were evaluable in 105/158 patients, with a pooled total of 216 treatment events recorded. Matched treatment was administered in 47/216 (22%) events and associated with prolonged median progression free survival (PFS) of 21.0 weeks (95% confidence interval [CI] 11.7-26.0 weeks) versus 12.1 weeks (95% CI 10.0-15.4 weeks) in unmatched, hazard ratio (HR) for progression or death 0.63 (95% CI 0.41-0.97; p=0.034). In the subgroup of PIK3/AKT/PTEN-altered MBC, HR for progression or death was 0.57 (95% CI 0.35-0.92; p=0.02) favouring matched treatment. Per-patient overall survival (OS) analysis (n=105) showed improved survival for patients receiving matched treatment versus unmatched, mOS 30.1 versus 11.8 months, HR=0.45 (95% CI: 0.24, 0.84; p=0.013). Objective response rate (ORR) in the overall population was similar in matched and unmatched treatment events (23.7% versus 17.2%, odds ratio of response 1.14 95% CI 0.50, 2.62; p=0.75). Conclusion Broad panel NGS sequencing in MBC is feasible, allowing therapeutic matching which was associated with improvements in PFS and OS.